Asb2α–Filamin A Axis Is Essential for Actin Cytoskeleton Remodeling During Heart Development. Issue 6 (16th March 2018) - Métais, Arnaud; Lamsoul, Isabelle; Melet, Armelle; Uttenweiler-Joseph, Sandrine; Poincloux, Renaud; Stefanovic, Sonia; Valière, Amélie; Gonzalez de Peredo, Anne; Stella, Alexandre; Burlet-Schiltz, Odile; Zaffran, Stéphane; Lutz, Pierre G.; et al.
Abstract : Rationale: : Heart development involves differentiation of cardiac progenitors and assembly of the contractile sarcomere apparatus of cardiomyocytes. However, little is known about the mechanisms that regulate actin cytoskeleton remodeling during cardiac cell differentiation. Objective: : The Asb2α (Ankyrin repeat-containing protein with a suppressor of cytokine signaling box 2) CRL5 (cullin 5 RING E3 ubiquitin ligase) triggers polyubiquitylation and subsequent degradation by the proteasome of FLNs (filamins). Here, we investigate the role of Asb2α in heart development and its mechanisms of action. Methods and Results: : Using Asb2 knockout embryos, we show that Asb2 is an essential gene, critical to heart morphogenesis and function, although its loss does not interfere with the overall patterning of the embryonic heart tube. We show that the Asb2α E3 ubiquitin ligase controls Flna stability in immature cardiomyocytes. Importantly, Asb2α-mediated degradation of the actin-binding protein Flna marks a previously unrecognized intermediate step in cardiac cell differentiation characterized by cell shape changes and actin cytoskeleton remodeling. We further establish that in the absence of Asb2α, myofibrils are disorganized and that heartbeats are inefficient, leading to embryonic lethality in mice. Conclusions: : These findings identify Asb2α as an unsuspected key regulator of cardiac cell differentiation and shed light on the molecular and cellular mechanisms determining the onset of myocardial cell architecture and its link with early cardiac function. Although Flna is known to play roles in cytoskeleton organization and to be required for heart function, this study now reveals that its degradation mediated by Asb2α ensures essential functions in differentiating cardiac progenitors. Abstract : Supplemental Digital Content is available in the text.